SITUASI PERAWAT PEGAWAI TIDAK TETAP DI DAERAH TERPENCIL PEGUNUNGAN MERATUS KABUPATEN HULU SUNGAI TENGAH â SEBUAH EVALUASI TERHADAP IMPLEMENTASI KEBIJAKAN - Dwi Handono Sulistyo, Rahmatullah Laksono Trisnantoro (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: The operation of mobile health center activitiesis currently unable to increase the coverage and provide equaldistribution of basic health service for people in isolated areas.The cost for mobile health center activities is relativelyhigh; it needs lots of staff and the service hours are limited. Asthe budget for mobile health center operation is limited, thefrequency of mobile health center activities is relatively low.Further consequence is that the implementation of survaillanceand priority program is constrained. To improve health servicefor people living in isolated areas of Meratus Mountain theDistrict Government of Hulu Sungai Tengah in 2002 issued apolicy on Non Permanent Staff Nurses. This policy is aimed toprovide continuous and accessible basic health service forthe community whenever they need it.Method: This was a descriptive qualitative study that used acase study design and was carried out at 4 villages that gotallocation of non permanent staff nurses with as many as 14informants. Primary data were obtained from indepth interviewwhereas secondary data were obtained from documentsearch particularly documents at Hulu Sungai Tengah districthealth office and health centers. Observation was also madeto get information not covered in indepth interview.Result: The result shows improvement in availability of basicservices to the community. On the other hand limited facilitiesare made available to the non permanent staff nurses, alongwith inadequate equipment, supplies, and vehicle to do theirwork. Also there is lack of additional incentive and regularmonitoring to support them.Conclusion: Basic health service was available more continuouslyand more accessible for people at isolated areas.However, findings also suggest that the policy of non permanentstaff nurses for isolated areas of Meratus Mountain, Districtof Hulu Sungai Tengah had not been fully supported bynecessary facilities, equipment, additional incentives and monitoring.Keywords: policy evalution, non permanent staff nurses, isolatedareas,